The protagonism of nursing in a center surgical/obstetric COVID-19 in care adaptations: Experience report (Research, Society and Development, 2021)
Objective: to describe the protagonism of nurses in the face of their experience in adapting a unit to attendance for pregnant and postpartum women with coronavirus. Methodology: descriptive and retrospective field study, developed through the experience report of nurses facing the adaptations made in a surgical/obstetric center between 2020 and 2021. Results: the new surgical/obstetric center was adapted from a pre-existing physical structure to promote the isolation of symptomatic and asymptomatic patients with coronaviruses from other patients and healthcare professionals. The protagonism of nurses in this process is evident when they were present in the decision-making process in view of the necessary changes, in the execution and reformulation of care flows, in the structural adjustments carried out in the unit, in addition to the training provided to the team and in the redistribution of the quantity of staff to meet the demand in the care of the new unit, as the same team now serves two different units, the surgical center, and now also the new COVID-19 surgical/obstetric center. Conclusion: nurses played a fundamental role in the entire process of structuring and direct patient care, highlighting their potential as a protagonist in the health care process.